SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN LOKASI BUDIDAYA IKAN KUWE DI KABUPATEN KEPULAUAN SANGIHE MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Oxila Afriani Senen; Alfrianus Papuas; Abraham Kamal (Jurnal Ilmiah Behongang, 2018)
In addition to the seed availability, food, market, and price, the selection of a good and right cultivation site can be one of the important factors in the business of sea cultivation. The selection of the location needs to consider on environmental factors and water quality.Process on determining a proper and improver site for fish sea fish cultivation can only rely on the intuition in selecting the location for sea fish cultivation, because there is still lack of data and environmental information about the proper waters. Therefore, there must be an early analysis on determining a proper location and an ideal water condition. This research aims at designing and building a supporting system on the feasibility of the cultivation site of Kuwe fish in Sangihe islands using Simple Additive Weighting (SAW) method, in which this method is oftenknown as the method of weighted totaling. A basic concept on this method is to figure out the weighted totaling of the work rating on every alternative of all atributes. This method needs the process of matrix normalization of decision (X) into a comparable scale with all available alternative ratings. This applicationis built by using programming terms of C++ on the Qt Creator and MySQL as database. This application is able to process data in the calculation of criteria and to be an alternative or choice for students and lecturer in determining the proper site for the cultivation of Kuwe fish in the regency of Sangihe islands.